Lepidium yelarbonense (Lepidieae; Brassicaceae), a new species from Australia - Al-Shehbaz, Ihsan A. (Phytotaxa, 2023)
Lepidium yelarbonense is a new Australian species described from a pair of collections made near Yelarbon (Queensland). It is confused with L. monoplocoides, from which it is easily distinguished by the perennial habit, lack of indumentum, subterete to hardly flattened fruiting pedicels, obtuse fruit valves not constricted subapically, and styles subequal to slightly exserted from the apical fruit notch.